Screening of phytochemical and antibacterial potential of diff erent organic solvent extracts of Stoechospermum marginatum (Ag) Kutz. from Manappad coast, Tuticorin District, South India - S. Krishnamoorthy, V. Venkatesalu, G. Adaikala Raj, M. Chandrasekaran (Journal of Medicinal Herbs and Ethnomedicine, 2015)
The antibacterial activity of different extracts of hexane, chloroform, ethyl acetate, acetone and methanol extract of a brown alga, Stoechospermum marginatum (Ag) Kutz. against Bacillus subtilis, Streptococcus pyogenes, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella typhimurium, Shigella flexneri and Vibrio cholerae. The extent of the inhibitory zone, Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined. The ethyl acetate extract of S. marginatum showed the highest antibacterial activity against all the bacterial strains tested than the other extracts. The mean zones of inhibition produced by the extracts in agar diffusion assays against the tested bacterial strains ranged from 7.1 to 18.1 mm. The MIC were between 125 and 500 Î¼g/ml, while the MBC were between 250 and 1000 Î¼g/ml. The ethyl acetate extract of S. marginatum showed the presence of terpenoids, tannins, phenolic compounds and steroids strongly than the other solvent extracts. The highest mean of zone inhibition (18.1 mm) was observed in the ethyl acetate extract of S. marginatum against B. subtilis. These finding suggest that the ethyl acetate extract of S. marginatum can be used as an antibacterial substance for the treatment of bacterial infections.